2019
DOI: 10.1186/s12909-019-1731-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors influencing the guide to read biomedical English literature course for Chinese new medical postgraduates—a multiple regression analysis

Abstract: Background There is a dearth of published literature that demonstrates the impact of a Guide to Reading Biomedical English Literature course on new Chinese medical postgraduates. Keeping this gap in mind, the objectives of this study were to assess the factors associated with course effectiveness using the teacher, postgraduate and organizational factors. Methods This study was conducted at Nanjing Medical University from December 2014 to December 2015. The participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In previous studies, the effect size measured by odds ratio for the predictors turned to be at least 1.5 (Catalano, 2015;Xu et al, 2019;Yen & Liu, 2009). With this reference, did the estimation of the sample size using G*Power 3.1.9.4, in which four values of odds ratios (1.5, 2.0, 2.5, and 3.0) were set to calculate the minimum sample sizes, resulting in the sample sizes of 637, 225, 134, and 96 for the four odds ratios respectively.…”
Section: Reference Of Priori Power Analysis and The Sample Sizementioning
confidence: 93%
“…In previous studies, the effect size measured by odds ratio for the predictors turned to be at least 1.5 (Catalano, 2015;Xu et al, 2019;Yen & Liu, 2009). With this reference, did the estimation of the sample size using G*Power 3.1.9.4, in which four values of odds ratios (1.5, 2.0, 2.5, and 3.0) were set to calculate the minimum sample sizes, resulting in the sample sizes of 637, 225, 134, and 96 for the four odds ratios respectively.…”
Section: Reference Of Priori Power Analysis and The Sample Sizementioning
confidence: 93%
“…Studies related to course effect in other fields involve the influence of various types of factors on course effect, such as teacher factors [42][43][44], teaching modes [45][46][47][48], etc. Some of the findings are consistent with this paper; for example, 95.5% of the people in Xu's study believed that appropriate course content was helpful for learning and research, and the course effect was related to the level of teachers [44]. This corroborates the findings of this study.…”
Section: Course Effectmentioning
confidence: 99%
“…1, April, 2019 because all the predictors were assumed to enhance learning. For the effect size, we examined previous studies (Catalano, 2015;Xu et al, 2019;Yen & Liu, 2009) and estimated the effect size measured by odds ratio for the predictors to be at least 1.5. We expected that if the null hypothesis is true, the probability of an event (=success) under X=1 is .5.…”
Section: Priori Power Analysis To Determine the Sample Sizementioning
confidence: 99%
“…Findings from Catalano (2015) showed that the odds ratio of transfer for a student in the situated learning environment to a student in the traditional instruction condition was 2.9. Xu et al (2019) studied the effect of teacher factors, individual factors, Volume 12, No. 1, April, 2019 and course management factors on student's perception of teaching effectiveness.…”
Section: The Effect Sizementioning
confidence: 99%
See 1 more Smart Citation